Kadına Yönelik Şiddet Araştırmaları: 2000 Yılı ve Sonrası İçin Bibliyometrik Bir Analiz - (:unkn) unknown (My University, 2016)
Bu çalışmada, Kadına Yönelik Şiddet konusunda 2000 yılı itibariyle ortaya konulan akademik katkı ölçülmeye çalışılmıştır. Araştırmanın veri seti, Web Of Science (WOS) veri tabanı üzerinden "violence against women" anahtar kelimesi ile derlenen makalelerden oluşturmaktadır. Sözkonusu makaleler, 2000 yılından itibaren beşer yıllık periyodlar için yıl bazındaki sıklık, ilgili oldukları alan, yayınlandıkları dergi, ülke, kurum ve yazarlar yönünden bibliyometrik olarak analiz edilmiş; ülkeler, kurumlar ve yazarlar arasındaki sosyal ağ yapısı ortaya çıkarılmıştır. 2000'den bu yana akademisyenlerin Kadına Yönelik Şiddet konusuna olan ilgisinde monoton bir artış olduğu gözlenmiştir. Bu konudaki araştırmalarda lider ülkenin ABD olduğu anlaşılmaktadır. Özellikle 2010 ve sonrasında Kadına Yönelik Şiddet konusunda çalışan üniversiteler ve yazarlar arasında akademik işbirliğinin yoğunlaştığı göze çarpmaktadır. Üniversiteler ve yazarlar için tespit edilen sosyal ağların, Kadına Yönelik Şiddet konusunda ileride gerçekleştirilecek akademik organizasyonlar için önemli bir enformasyon sağlayacağı düşünülmektedir

The purpose of this study is to measure the existing scientific contribution on the subject of “violence against women (VAW)” since 2000. The data set of this research is compiled of the articles searched by the keyword “violence against women” on Web of Science (WOS) data base. These articles were analyzed bibliometrically according to their annual frequency, field of interest, country, institution, journals they were published in and their authors in five-year periods since 2000. Besides the social network among countries, institutions and authors contributed to the VAW literature was disclosed. It is observed that there had been a significant increase in the scientists’ interest on the subject of VAW since 2000. It is also remarkable that the USA stands out as the leading country on this subject in all the three periods. The academic cooperation between the authors and the universities that are studying on the subject of VAW has been improved especially starting from 2010. It is believed that the obtained data in this study and presented social network structures among countries, universities and authors would serve as a guide for the improvement of future international cooperative works among the leading universities and researchers that study to protect the women against the violence
RESEARCHES ON THE SUBJECT OF “VIOLENCE AGAINST WOMEN”: A BIBLIOMETRIC ANALYSIS SINCE 2000
Keywords: İktisat; İşletme